EFFECT OF LABOR ANALGESIA IN PREGNANT WOMEN AND NEWBORN - Paredes Goycochea, Luis (2015)
OBJETIVES: To evaluate the effects of epidural analgesia in the mother during labor and the newborn. DESIGN: A retrospective case control study was conducted. Methods: Study of 153 cases of childbirth with analgesia and 73 cases in the control group, population sample with p <0.05. RESULTS: The rate of expansion was 2.27 cm per hour for the control group and 4.7 cm per hour for labor analgesia group, with statistically significant difference p <0.01. The second stage was 13.904 minutes in the control and statistically significant in the group 16.132 minutes of delivery with analgesia group difference with p <0.01. In the newborn, the Apgar minute was 8.7 and 8.5 in the control group in the delivery with analgesia, and five minutes 9.0 and 8.9 in the control group in the delivery with analgesia , both without significant difference. Respiratory depression in the control group was 2.7% and 3.9% in the group with analgesia labor and income to the neonatal intensive care unit 1.4% and 1.9%, respectively. CONCLUSIONS: labor analgesia shortens the period of expansion and extends the expulsion period, unchanged from the results in the newborn.